Asset transfer requests : evaluation of part 5 of the Community Empowerment (Scotland) Act 2015 /: evaluation of part 5 of the Community Empowerment (Scotland) Act 2015. (2020) - McMillan, Carolyn; Steiner, Artur; Hill-O'Connor, Clementine
No abstract available